2020
DOI: 10.1108/ijchm-03-2019-0265
|View full text |Cite
|
Sign up to set email alerts
|

Role of virtual avatars in digitalized hotel service

Abstract: Purpose This study aim to attempt to conceptualize agency in a hospitality setting and examine the psychological effects of agency-related visual cues on user perception and intention to use to understand the role of agency in the digitalization of hotel services. Design/methodology/approach After developing demo videos of an express check-out application, two experiments were conducted to examine the effects of using an avatar and explain the psychological mechanism of how attributes of an avatar increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 46 publications
3
37
1
Order By: Relevance
“…Fourth, the analyses revealed that positive consumer attitude significantly affects intention to use, supporting previous research (Ajzen, 1991). Choi et al (2020) found that avatars had a positive effect on their intended use and explained the psychological mechanisms of how avatars affect intention to use. Fifth, the analyses results confirmed perceived value’s influence on the intention to use robot-serviced restaurants.…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, the analyses revealed that positive consumer attitude significantly affects intention to use, supporting previous research (Ajzen, 1991). Choi et al (2020) found that avatars had a positive effect on their intended use and explained the psychological mechanisms of how avatars affect intention to use. Fifth, the analyses results confirmed perceived value’s influence on the intention to use robot-serviced restaurants.…”
Section: Discussionmentioning
confidence: 95%
“…Academic discussions on the topic (Castillo et al , 2020; Choi et al , 2020; Huang and Philp, 2020; Loureiro et al , 2020) have focused on automation processes (Tussyadiah, 2020), ethical issues related to AI and service robots (Belanche et al , 2020b; Belanche et al , 2020). For instance, some researchers have examined the antecedents of chatbot adoption by travelers (Pillai and Sivathanu, 2020), while others have investigated guests’ attitudes and adoption intentions toward robot concierges (Shin and Jeong, 2020) or explored how robotic anthropomorphism orientation affects the way customers judge the service encounter (Zhu and Chang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most hospitality service robot research is conducted in general service or hotel settings (Belanche et al , 2020a; Choi et al , 2020; Shin and Jeong, 2020). The few studies in the restaurant context (Belanche et al , 2020b; Cha, 2020; Zemke et al , 2020) have focused on consumers’ intention to use or perceptions before the actual service stage.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%